1980
DOI: 10.1073/pnas.77.8.4938
|View full text |Cite
|
Sign up to set email alerts
|

Active site amino acid sequence of human factor D.

Abstract: C3 and C5 (3-6). Factor B has recently been characterized as a serine protease (11). Factor D is thus required for alternative pathway activation (4,(12)(13)(14). Its activity is inhibited by diisopropyl phosphorofluoridate (iPr2P-F) (7-9), and its NH2-terminal amino acid sequence is homologous with the NH2-terminal sequences of the serine proteases (15, 16). However, this enzyme differs from other plasma proteases in several characteristics. Factor D probably circulates in its active proteolytic form. The dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1982
1982
1998
1998

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 35 publications
1
1
0
Order By: Relevance
“…Residue 24 was identified as histidine, 48 as aspartic acid, and 50 as lysine. This is in agreement with the work of Davis et al (1979Davis et al ( , 1980 but differs from the glutamic acid, glycine, and tyrosine determinations, respectively, published by Reid et al (1981) at these positions. In addition, we have identified residue 38 as serine, residue 58 as threonine, residue 112 as glutamine, residue 154 as threonine, and residue 213 as threonine, whereas Reid et al (1981) have identified threonine, isoleucine, glycine, lysine, and serine, respectively, at these positions.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Residue 24 was identified as histidine, 48 as aspartic acid, and 50 as lysine. This is in agreement with the work of Davis et al (1979Davis et al ( , 1980 but differs from the glutamic acid, glycine, and tyrosine determinations, respectively, published by Reid et al (1981) at these positions. In addition, we have identified residue 38 as serine, residue 58 as threonine, residue 112 as glutamine, residue 154 as threonine, and residue 213 as threonine, whereas Reid et al (1981) have identified threonine, isoleucine, glycine, lysine, and serine, respectively, at these positions.…”
Section: Discussionsupporting
confidence: 90%
“…The study of D has been hampered by its low serum concentration and by the difficulty in removing contaminants of similar apparent molecular weight and behavior on ion-exchange chromatography (Johnson et al, 1980). Recently, however, several reports have appeared in the literature detailing the isolation of purified D in sufficient quantities to carry out partial amino acid sequence analysis (Davis et al, 1979;Volanakis et al, 1980;Davis, 1980;Johnson et al, 1980;Reid et al, 1981). We now report the determination of the essentially complete amino acid sequence of this key complement component.…”
mentioning
confidence: 99%